The anti-diabetic effect of eight Lagerstroemia speciosa leaf extracts based on the contents of ellagitannins and ellagic acid derivatives. Issue 2 (31st January 2020) - Guo, Sen; Ren, Xiameng; He, Kan; Chen, Xiaozhuo; Zhang, Shanshan; Roller, Marc; Zheng, Bolin; Zheng, Qunyi; Ho, Chi-Tang; Bai, Naisheng
Abstract : Anti-diabetic effects of eight extracts from leaves of L. speciosa using different manufacturing processes based on the contents of active ellagitannins and inhibitory ellagic acid derivatives. Abstract : Previously, we have reported the opposite effects of compounds isolated from Lagerstroemia speciosa leaves on a glucose transport (GLUT4) assay. Ellagitannins from L. speciosa activated GLUT4, while ellagic acid derivatives showed an inhibitory effect. As part of our continuing research on anti-diabetic nutritional supplements, we herein compared the anti-diabetic effects of several extracts (LE1–8 ) from leaves of L. speciosa using different manufacturing processes based on the contents of ellagitannins and ellagic acid derivatives. Their anti-diabetic effects were evaluated through glucose uptake and adipocyte differentiation in 3T3-L1 cells in vitro as well as alloxan induced diabetic mice in vivo . These extracts were given to mice by gavage at doses of 0.25, 1.0, and 4.0 g per kg body weight once a day for 21 consecutive days. Results showed that LE1 (1.0 g kg −1 ), LE3 (1.0 or 4.0 g kg −1 ), LE4 (1.0 or 4.0 g kg −1 ), LE5 (0.25 or 1.0 or 4.0 g kg −1 ) and LE7 (1.0 or 4.0 g kg −1 ) showed significant anti-diabetic effects in alloxan-induced diabetic mice as indicated by the decreased levels of fasting blood glucose, body weight, serum biomarkers, tissue weight and body fat, and increased final insulin levels. LE8 (1.0 g kg −1 ) showed a moderate anti-diabetic effect as illustrated by the reduced fasting blood glucose level while LE2 and LE6 showed slight effects in alloxan-induced diabetic mice. The potential correlation of the content of ellagitannins, ellagic acid derivatives, and corosolic acid with the anti-diabetic activity was discussed.